Implementasi Forward Chaining Dan Breadth First Pada Sistem Pakar Diagnosa Gangguan Kehamilan - Widiastuti, Sri Handani (JSAI (Journal Scientific and Applied Informatics), 2019)
Expert system is a computer-based system that uses knowledge, facts and reasoning techniques in solving problems that can usually only be solved by an expert. Inference method is a thinking mechanism and reasoning patterns used by the system to reach conclusions, while forward chaining is an inference method that traces starting from a set of facts by looking for rules that match the guesswork / hypothesis that leads to conclusions. Expert systems can be applied in various fields, including in medicine, for example how to diagnose a disease. Pregnancy is a happy moment for a mother, but there are still many problems with pregnancy problems in pregnant women because many do not know about pregnancy disorders that usually occur. Puskesmas Bontang Utara I has a program to reduce mortality in pregnant women and infants, by providing guidance and socialization on how to maintain a correct pregnancy. To facilitate public understanding and provide information related to pregnancy disorders, the researchers made the application system expert pregnancy disorders built using the PHP programming language, Dreamweaver 8 as an editor and MySql as the database. Software development methods use the waterfall model and system testing using blackbox. The expert system application in this study provides information on diagnosing pregnancy disorders in pregnant women such as consulting with experts. The diagnostic process starts with the way the user selects or inputs the type of complaint that is felt in accordance with the symptoms provided by the system. By using the forward chaining method and breadth first search search technique, the complaints that have been entered will be matched with the symptoms and types of disturbances stored in the database. So that the results of the diagnosis will be produced as the results of the diagnosis of experts. With this information helps pregnant women recognize pregnancy disorders during pregnancy.